Proneurogenic Actions of FSH During Directed Differentiation of Neural Stem and Progenitor Cells from Ovarian Cortical Cells Towards the Dopaminergic Pathway - Alfredo González-Gil; Concepción Rojo; Esther Ramírez; Ricardo Martín; Alberto Samuel Suárez-Pinilla; Susana Ovalle; Ricardo Ramos-Ruiz; Rosa Ana Picazo (Biomedicines)
Exploring the neurogenic potential of extraneural stem cells under the actions of proneurogenic biomolecules may enhance the success of autologous cell therapy for neurodegenerative diseases such as Parkinson’s. Neural stem and progenitor cells (NSPCs) from extraneural tissues have emerged as potential sources of functional dopaminergic (DA) neurons. Background/Objectives: This study aimed to generate DA neurons from ovarian cortical cells (OCC)-derived NSPCs to elucidate whether follicle-stimulating hormone (FSH) can enhance this process and to evaluate the electrophysiological functionality of differentiated neural cells using the patch-clamp technique. Methods: OCC-NSPCs were differentiated towards the DA pathway during the neurosphere (NS) assay after two culture periods for cell expansion (CEP-1, CEP-2) with one of these media: M1 (positive control with epidermal growth factor, EGF, and fibroblast growth factor2, FGF2), M2 (control), and M3 (M2 with FSH, 50 ng/mL). Image analysis, morphometric evaluation, cell proliferation assays, and gene expression analysis of NSPC-specific transcripts were performed. After CEP-2, NS cells were cultured for 30 days in a serum-free medium containing Sonic-Hedgehog, FGF2, FGF8, and brain-derived neurotrophic factor (BDNF) for differentiation. At the end of culture, expression, and immunolocalization of GFAP, Olig2, NeuN, and tyrosine hydroxylase (TH) were analyzed in cells, along with patch-clamp recordings in differentiated neurons. Results: Cell proliferation and NS development were larger in OCC-NSPCs from groups M1 and M3 than in M2. Expression of NSPC-related transcripts was higher in M2; however, M1 and M3 cultures showed greater expression of differentiation markers NeuN, GFAP, Olig2, and TH. NeuN, GFAP, and TH were immunolocalized in differentiated cells and NS that were generated during differentiation. TH was localized in neural precursor cells, some neurons, core cells of small-, medium-, and large-sized NS, and in cells close to the outer cell layer of large NS, with greatest immunolocalization percentages in NS primed with FSH during CEP-1/2 (M3). Electrophysiological recordings revealed a major incidence of plateau potentials and a significant proportion of complete action potentials, reflecting successful functional neuronal differentiation. Conclusions: DA precursors and functional neurons can be successfully obtained after OCC-NSPCs-directed differentiation. FSH priming during the expansion period enhances the neurogenic potential of these cells towards the DA pathway. Future research will explore the eventual therapeutic use of these findings for neurodegenerative diseases.